UMP signs SARE agreement with TNB and GSPARX - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 15 March 2023 - Universiti Malaysia Pahang (UMP) signed a supply agreement with renewable energy (SARE) with Tenaga Nasional Berhad (TNB) and TNB Renewables’ wholly-owned subsidiary, GSPARX Sdn. Bhd. in a recent ceremony at the UMP Pekan Banquet Hall.